Simultaneous co-assembly of fenofibrate and ketoprofen peptide for the dual-targeted treatment of nonalcoholic fatty liver disease (NAFLD). Issue 36 (2nd April 2020) - Wang, Zhongyan; Ma, Chuanrui; Shang, Yuna; Yang, Lijun; Zhang, Jing; Yang, Cuihong; Ren, Chunhua; Liu, Jinjian; Fan, Guanwei; Liu, Jianfeng
Abstract : An ingenious co-assembled nanosystem based on fenofibrate and ketoprofen peptide for the dual-targeted treatment of NAFLD by reducing hepatic lipid accumulation and inflammatory responses. Abstract : We have developed a co-assembled nanosystem based on fenofibrate and ketoprofen by tactfully utilizing their simultaneous benzophenone interaction, which greatly enhances the bioavailability of fenofibrate and plays a role in the dual-targeted treatment of NAFLD by reducing hepatic lipid accumulation and inflammatory responses.